2010
DOI: 10.1182/blood-2010-02-266296
|View full text |Cite
|
Sign up to set email alerts
|

An antibody against the colony-stimulating factor 1 receptor depletes the resident subset of monocytes and tissue- and tumor-associated macrophages but does not inhibit inflammation

Abstract: The development of the mononuclear phagocyte system requires macrophage colony-stimulating factor (CSF-1) signaling through the CSF-1 receptor (CSF1R, CD115). We examined the effect of an antibody against CSF1R on macrophage homeostasis and function using the MacGreen transgenic mouse (csf1r-enhanced green fluorescent protein) as a reporter. The administration of a novel CSF1R blocking antibody selectively reduced the CD115 ؉ Gr-1 neg monocyte precursor of resident tissue macrophages. CD115 ؉ Gr-1 ؉ inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

44
419
5
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 430 publications
(470 citation statements)
references
References 50 publications
44
419
5
2
Order By: Relevance
“…We have recently reported that the administration of CSF-1R blocking antibody selectively reduced monocyte precursors of resident tissue macrophages. 67 The current study suggests that CSF-1 acts, at least in part, through production of IGF-1 by kidney macrophages. We further propose that an activation of CSF-1 by tissue macrophages creates a microenvironment that influences the growth, proliferation, and differentiation of renal epithelial cells and promotes matrix remodeling and Figure 9.…”
Section: Discussionmentioning
confidence: 57%
“…We have recently reported that the administration of CSF-1R blocking antibody selectively reduced monocyte precursors of resident tissue macrophages. 67 The current study suggests that CSF-1 acts, at least in part, through production of IGF-1 by kidney macrophages. We further propose that an activation of CSF-1 by tissue macrophages creates a microenvironment that influences the growth, proliferation, and differentiation of renal epithelial cells and promotes matrix remodeling and Figure 9.…”
Section: Discussionmentioning
confidence: 57%
“…A recent study, however, reported that the number of circulating monocytes was not reduced in M-CSF-deficient mice (6). Consistently, Ab blocking of CSF1R in mice selectively inhibited monocyte maturation in the periphery without affecting their numbers (30). Despite these discrepancies, current evidence suggests that M-CSF is likely involved in the maturation and survival rather than the production of monocytes in mice.…”
Section: Discussionmentioning
confidence: 58%
“…Like most tissue Mjs, these cells are dependent upon CSF-1 [11] and are absent in mice lacking CD115 (CSF-1R) [46]. According to the current dogma, these resident Mjs should derive from Ly6C low monocytes [47], but adoptive transfer experiments show that Ly6C high monocytes can give rise to both CX3CR1 low/int (''inflammatory'') and CX3CR1 high (''resident'') MPs in the 'steady-state' intestine (Fig.…”
Section: Origins Of Intestinal Macrophagesmentioning
confidence: 99%